Some quality properties of tropical cucurbits Chayote (Sechium edule (Jacq)Sw.), Bitter melon (Momordica chararantia L.) and Kiwano (Cucumis metuliferus E. Mey) produced in the temperate climate conditions of North Macedonia - Trajche Dimitrovski; Danica Andreevska; Dobre Andov; Natasha Gjorgovska; Vesna Levkov (Research Institute of Mountain Stockbreeding and Agriculture, Troyan, 2020)
The tropical crops chayote, bitter melon and kiwano (Cucurbitaceae) were cultivated under the temperate continental sub-Mediterranean climate of Kochani region, North Macedonia. The fresh fruitswere tested for their physicochemical characteristics (water content, total dry content, total soluble solids and pH) and microbiological quality using selective media for Salmonella spp., L.monocytogenes, E. coli/Enterobacteriaceae, yeast and molds and plate count agar for total number of bacteria. All parameters were tested in 5 replications. The physicochemical properties of kiwano (total soluble solids of 4.07 %Brix and pH of 4.47) and bittermelon (total soluble solids of 3.77 %Brix) were similar to reports from otherregions/countries, while the chayote had a similar water content and pH but lower total soluble solids obtained in ourconditions. Concerning the microbiological quality, L. monocytogenes, Salmonelaspp. and E. coli were not detected in any of the samples. Non-coli Enterobacteriaceae were found in kiwano and bitter melon.The highest average plate count was found in kiwano (3626 cfu/g) while the highest number of yeasts and molds in bitter melon (3084 cfu/g). The results suggest that chayote, bitter melon and kiwano crop with good fruit quality can be produced under the temperate climate conditions of North Macedonia. Still, the chayote had inferior total soluble solids as compared to the crop produced in tropical and subtropical regions.The research in these crops should continue in regard to the suitability of thedifferent climate-vegetation-soil regions for their cultivation, and specific cultivation techniques in each species in relation to fruit yield and quality.
Keywords: Sechium edule, Momordica charantia, Cucumis metuliferus, microbiological criteria; physicochemical properties